Plant-based vaccines for poultry viral diseases: Avian influenza - Elbohy, Ola Assem Mohamed Saleh (2023)
Avian influenza virus (AIV) is a significant reason for mortality in poultry,causing substantial economic loss. The importance of AIV is increased due to the ability of several subtypes to cause zoonotic infection, with, in the case of H5N1, mortality rates approaching 60%. Haemagglutinin (HA) is the main antigen of AIV, and protecting antibodies are elicited against it in the host after viral infection. Control of viral diseases in poultry depends mainly on vaccination and high biosecurity levels.